1985
DOI: 10.1073/pnas.82.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of a fatty acid binding protein in rat liver plasma membranes.

Abstract: When [14C]oleate-bovine serum albumin complexes were incubated in vitro with rat liver plasma membranes (LPM), specific, saturable binding of oleate to the membranes was observed. Maximal heat-sensitive (i.e., specific) binding was 3.2 nmol/mg of membrane protein. Oleateagarose affinity chromatography of Triton X-100-solubilized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
191
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 310 publications
(197 citation statements)
references
References 37 publications
5
191
0
1
Order By: Relevance
“…That these proteins are similar and mediate FFA uptake has been clearly demonstrated. By immunofluorescence, an antibody raised in rabbits against the rat liver FABPpM bound specifically to the plasma membranes of cardiac myocytes, adipocytes, and jejunal enterocytes (12)(13)(14). This antibody also inhibited oleate uptake, noncompetitively and in a dosedependent fashion, in rat hepatocytes (9), adipocytes (12) and, in preliminary studies, in the gut (15).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…That these proteins are similar and mediate FFA uptake has been clearly demonstrated. By immunofluorescence, an antibody raised in rabbits against the rat liver FABPpM bound specifically to the plasma membranes of cardiac myocytes, adipocytes, and jejunal enterocytes (12)(13)(14). This antibody also inhibited oleate uptake, noncompetitively and in a dosedependent fashion, in rat hepatocytes (9), adipocytes (12) and, in preliminary studies, in the gut (15).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we and others have shown that FFA uptake has the kinetic characteristics of a carrier-mediated process in hepatocytes (8,9) and adipocytes (10)(11)(12), and have isolated and characterized basic, 40-kD FABPpM from these and other tissues with high transmembrane fluxes of fatty acids (13,14,20). That these proteins are similar and mediate FFA uptake has been clearly demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations